Cytochemical localization and quantification of plasma membrane Ca2+-ATPase activity in mollusc digestive gland cells - Pons, G; Evangelisti, V; Caprì, F; Mozzone, S; Viarengo, A (European Journal of Histochemistry, 2009)
A cytochemical method allowing the localization and quantification of plasma membrane Ca2+- ATPase (PMCA) in frozen sections obtained from digestive gland cells of Mytilus galloprovincialis, Tapes tapes and Chamelea gallina, is presented. The method utilizes lead as a trapping agent of PO4 2- ions released by Ca2+-ATPase activity. The amount of lead sulphide precipitate proportionally related to PMCA activity was quantified by a light microscopy digital imaging analysis system. The optimal assay conditions of Ca2+-ATPase activity evaluated at pH 7.4 were: 200μM free Ca2+, 200mM KCl, 2 mM ATP, and under such analysis conditions the enzyme showed a linear trend up to 60 min (at 20ºC). The PMCA activity was substrate specific: ADP was utilized only at a low rate (24% with respect to an equimolar ATP concentration), while glucose-6-phosphate and b-glycerophosphate were poorly hydrolyzed. The enzyme activity was strongly inhibited by sodium ortho-vanadate. Our detection of a Ca2+-ATPase activity at nanomolar concentrations of free Ca2+ suggests that we have identified a plasma membrane Ca2+-ATPase involved in Ca2+ homeostasis. The Ca2+-ATPase was found to be localized in the basal part of the plasma membrane in the digestive gland cells of Mytilus galloprovincialis and Tapes tapes, but in the apical plasma membrane of Chamelea gallina. The possible implications of the different cellular distributions of PMCA activity is discussed.